Digest. - Gammage, Kim; Adam, Margo; Bird, Matthew; Blazo, Jordan; Ede, Alison; Hirsch, Katie; Lee, Seungmin; Locke, Sean; Stork, Matthew; Wierts, Colin; Zajonz, Pia (Journal of Sport & Exercise Psychology, 2025)
The article discusses the development of a conceptual model for digital cardiac rehabilitation, emphasizing the limitations of traditional intervention approaches that do not clarify the effectiveness of individual components. It introduces the Multiphase Optimization Strategy as a framework to identify impactful intervention elements while addressing constraints like cost and time. The study involved a systematic review, qualitative interviews with patients, and an analysis of international guidelines, leading to the creation of a model that connects behavior change techniques to their mechanisms and outcomes. The authors aim to enhance understanding and effectiveness in digital cardiac rehabilitation through this structured approach.